In Vitro Characterization of Nasal Spray to Asses Bioequivalence - Cheekti, Dilip Kumar.; Kumar, P.V. Tarun; Dhage, Ramrao; Gappa, Shambulin; Sahoo, Bikash (Asian Journal of Pharmaceutical Research and Development, 2021)
To layout the characterization of Nasal sprays and discuss the characterization method and sampling plan to assess the in -vitro bioequivalence of test product and reference product. The in -vitro bioequivalence study of nasal sprays are useful to understand the efficiency of test product in comparison to innovator so that the equivalency in the in -vivo studies can be assessed. The in -vitro bio equivalency characterization of nasal sprays helps us to correlate the efficiency of test product with respect to the reference product, so that the efficacy and safety can be achieved in par with Reference listed drug. The characterization studies include the product behavior throughout the unit life cycle. The nasal spray test includes the SAC, Priming, repriming, Spray pattern, plume geometry, Droplet size distribution and Drug in small particles.